Students' Politeness Strategies to Lecturers in Sending Messages through WhatsApp - Veronika Unun Pratiwi; Atikah Anindyarini (Budapest International Research and Critics University, 2021)
One of the issues that students face today is a lack of politeness in their language. Students' politeness is reflected in their attitudes when sending messages to lecturers. The objective of this study was to determine how polite students are when communicating with their lecturers through WhatsApp. This study was conducted at a private university in Sukoharjo. The data was obtained from student texts in the lecturer's WhatsApp app. The data was analyzed using Brown and Levinson's (1987) FTA theory on politeness strategies. According to the findings of the study, some students were found sending messages without greeting the lecturers and instead conveying their intentions directly. FTAs are common, and students frequently threaten the lecturers' faces. The words used in a student's message can have an effect on the teacher's feelings and make the conversation appear informal. Students appear to be unaware of social distance, roles and status, and power dynamics when interacting with lecturers. Some students treat lecturers as equals, which comes across as rude and disrespectful. It is strongly suggested that this topic be expanded upon and discussed in a broader context and area for future research. More research could look at this issue from a different perspective.